Electrocatalytic effect of Pb and Sn adatoms on the oxidation of 1-propanol on platinized platinum electrodes: Determination of the apparent activation energy - Giannetti, B. F.; Almeida, CMVB; Bonilla, S. H.; Mengod, MOA; Raboczkay, T. (R Oldenbourg Verlag, 2003)
The electrocatalytic oxidation of 1-propanol was investigated on platinum electrodes modified by submonolayers of Pb and Sn in acid media. An increase of oxidation rates observed for both Pb and Sn, and the influence of theta values was investigated. The values of the apparent activation energy evaluated from the Arrhenius plots concerning the electrochemical oxidation of 1-propanol on modified platinzed platinum electrodes, reveal a significant decrease in the presence of upd Sn and Ph adatoms. A decrease from 56 to 26 U mol(-1) in the presence of Sn. and from 78 to 25 U mol(-1) for Ph adatoms are some illustrative values which reflect the promoting effect of the upd adatoms.